Environmental Kuznets Curve in Greece in the period 1960-2014 - Kotroni, Erasmia; Kaika, Dimitra; Zervas, Efthimios (International Journal of Energy Economics and Policy, 2020)
CO2 emissions in Greece have increased significantly in recent decades. Many researches point out that Greek’s economy structure is characterized by a strong interdependence of energy use and economic growth, so that any increase in national production leads to an increase in CO2 emissions. In this sense, Greek’s economy structure does not allow policies to de-escalate the level of CO2 emissions without cost in terms of economic growth. This paper focuses on investigating the short and long term relationship between Gross National Product (GDP), CO2 emissions and gross energy use over the period 1960-2014, using appropriate econometric tools. Additionally, the impact of the urbanization rate on CO2 emissions is examined. The exploration of these relationships is part of the Kuznets Environmental Curve (EKC) theory that economic growth ultimately leads to a degradation of environmental degradation. Keywords: Kuznets Environmental Curve; CO2 emissions; energy use, Granger causality; Greece JEL Classifications: Q01, Q40, Q50, Q56 DOI: https://doi.org/10.32479/ijeep.9671